Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Joko Mariyono (Faculty of Economic & Business Universitas Gadjah Mada, 2013)
No. Penulis --- Judul Artikel --- Halamanrn1. Joko Mariyono --- Environmentally Adjusted Productivity Growth of Indonesian Rice Production --- 1-22rn2. Faizal Reza dan Tri Widodo 2. Faizal Reza dan Tri Widodo --- The Impact of Education on Economic Growth in Indonesia --- 23-44rn3. Lilis Nurul Husna dan Sarpono --- Spatial Small Area Estimation for Determination of Underdeveloped Villages in The Province of Yogyakarta (DIY) in 2011 --- 45-61rn4. Anthonius H. Citra Wijaya and Rusdi Akbar --- The Influence of Information, Organizational Objectives and Targets, and External Pressure Towards The Adoption of Performance Measurement System in Public Sector --- 62-83rn5. Sumiyana and Zaki Baridwan --- Accounting Fundamentals and Variations of Stock Price : Methodological Refinement with Recursive Simultaneous Model --- 84-114rn6. Wuryan Andayani dan Sony Warsono --- Prosoector-Defender Strategy, Auditor Industry Specialization, Earnings Management Through Real Activities, and Earnings Quality --- 115-131rn7. Indri Erkaningrum F. ---- Interactions Among Insider Ownership, Dividend Policy, Debt Policy, Investment Decision, and Business Risk ---- 132-148rn8. Adiwan F. Aritenang ---- The Role of Technology in Regional Development : TFP and Econometrics Analysis --- 149-158